Utilidad de la nebulización: tratamiento del asma bronquial en menores de 5 años que acuden al Subcentro Los Vergeles del Cantón Milagro periodo mayo – septiembre 2019. - Espinoza Quiñonez, Cindy Priscilla (2020)
This project was carried out in order to publicize the use of nebulization as a treatment for bronchial asthma. This research seeks to validate its usefulness as a complement in the treatment of bronchial asthma, because there is an increase in cases of children diagnosed with this respiratory condition. Since asthma is a chronic disease that affects people especially children under 5 years of age, it worsens at night and they cannot understand it because of their young age and all they do is cry, what leads parents to enter a high degree of stress for not knowing what to do. It is considered important the application of this process to identify the factors that cause respiratory infections, so it seeks to meet health needs thus considering an early intervention of the nebulization in respiratory pathologies checking its efficiency. The purpose of this research project is to demonstrate the usefulness of the nebulization in the treatment of bronchial asthma in children under 5 years of age who attend the Los Vergeles sub-center of the Milagro canton.